Functional morphology of the lungs of the green iguana, Iguana iguana, in relation of body mass (Squamata: Reptilia) - Peixoto, Danilo; Klein, Wilfried; Abe, Augusto Shinya [UNESP]; Cruz, Andre Luis da (Senckenberg Gesellschaft Naturforschung, 2018)
Body mass is one of the most influencing factors of metabolic rate and gas exchange of animals, and also related to activity pattern and occupancy of ecological niches. This study aimed to understand the relationships between body mass (M-B) and morpho-functional features of the lungs of Iguana iguana, through morphological and morphometric characterization of the structural elements of the respiratory system. Iguana iguana has lungs of the transitional type, the heterogeneously distributed parenchyma being faveolar in cranial and medial regions and trabecular in the caudal region. Within the parenchyma, 43.6 +/- 25.5% corresponds to faveoli, 18.0 +/- 5.9% to interfaveolar septa, and 38.7 +/- 31.6% to trabeculae. Within the interfaveolar septa, 9.4 +/- 4.0% corresponds to blood capillaries, 4.4 +/- 1.0% to type I pneumocytes and 3.9 perpendicular to 1.1% to type II pneumocytes. Allometric analyses showed that lung (M-B(0.8949)) and parenchymal volume (M-B(1.030)) scale with M-B in I. iguana just as in other lizards with unicameral or transitional lungs, which was unexpected for lung volume, since reptilian lung volume is generally considered to scale as M-B(0.75). The functional morphology of the lungs in I. iguana seems to play an important role to meet the metabolic demands through ontogenetic growth.
Keywords: Lizard; respiratory morpho-functionality; gas exchange